2019
DOI: 10.1016/j.ssmph.2019.100422
|View full text |Cite|
|
Sign up to set email alerts
|

Period and cohort-specific trends in life expectancy at different ages: Analysis of survival in high-income countries

Abstract: The number of older adults is increasing in high-income countries as survival chances continue to improve. We investigate changes in survival at older ages in high-income countries and show that although survival chances have improved, these improvements are concentrated at the top of the survival distribution where there is a small share of the population. Among females who survive to age 85 in the most recently birth cohort (1925), for example, about half die within 8 years while those in the top 25% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The gender distribution in the birth cohorts is based on the historic gender distribution in the given decade [ 17 ]. Improvements in survival of birth cohorts in the Netherlands are similar to those observed in other high-income countries [ 26 ], including the United States and the United Kingdom (see Appendix A for a direct comparison).…”
Section: Datasupporting
confidence: 67%
See 1 more Smart Citation
“…The gender distribution in the birth cohorts is based on the historic gender distribution in the given decade [ 17 ]. Improvements in survival of birth cohorts in the Netherlands are similar to those observed in other high-income countries [ 26 ], including the United States and the United Kingdom (see Appendix A for a direct comparison).…”
Section: Datasupporting
confidence: 67%
“…First, this model was developed on the basis of Dutch data. Although changes in population structure and relative reductions in dementia incidence are similar across high-income countries [ 6 , 26 ], this may hamper generalizability of the projections. Also, the Rotterdam Study population is predominantly White.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of providing projections for the Dutch population also presents another limitation. Although changes in population structure and relative reductions in dementia incidence are similar across high‐income countries, 27,47 this may hamper the generalizability of the projections. Furthermore, cost and quality‐of‐life estimates are often country specific and depend on a variety of factors, such as policy recommendations, family values, and accessibility of the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that con clu sions about com pres sion or dis per sion of deaths are heavily driven by reli ance on chro no log i cal age. Wilmoth and Horiuchi (1999), CanudasRomo (2008), and Beltrán-Sánchez and Subramanian (2019 alluded to this, whereas Zuo et al (2018) pro vided com pel ling evi dence of shifting pat terns in the age dis tri bu tion of deaths.…”
Section: Introductionmentioning
confidence: 99%
“…The selec tion of the onset age dis re gards the mor tal ity dynam ics at youn ger ages. Steady shifts in death per cen tiles start well before age 65 as there is evi dence that major reduc tions in death rates have taken place at youn ger ages (e.g., Beltrán-Sánchez and Subramanian 2019;BergeronBoucher et al 2015). Ages before and after 65 are both part of the same con tin u ous pro cess of aging.…”
Section: Introductionmentioning
confidence: 99%